Solution spillover: Pairing issues with ideological solutions fuels polarization - Adrienne M. Kafka; Troy H. Campbell; Aaron C. Kay (Proceedings of the National Academy of Sciences, 2025)
Recent research has focused on understanding ideological and affective political polarization in the United States; however, the polarization of issue salience—defined as personal beliefs about how important or concerning an issue is, and how much attention or priority it deserves—has garnered less attention, especially regarding its underlying causes. We propose that issue salience polarization, particularly that of ideologically neutral issues, is driven in part by two psychological processes: solution aversion (denying problem severity when solutions are introduced that conflict with political beliefs) and solution attraction (exaggerating problem severity when solutions are introduced that align with political beliefs). If this is so, we should be able to observe issues that are nonpolarized at baseline become suddenly polarized when paired with solutions that are consistent with a specific ideological position (liberal or conservative). Consistent with this prediction, four experimental studies demonstrate the emergence of issue salience polarization arising from solution aversion and solution attraction (Studies 1–4). Results also demonstrate support for the role of zero-sum beliefs, or the belief that one political party’s gains must come at the expense of the other party, in driving this process (Study 3).